Effects Of Reagentizing Temperature And Ionic Strength And Their Interactions In Hematite Flotation - R. D. Kulkarni; P. Somasundaran (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1978)
Reagentizing at elevated temperature, reported in the past as beneficial for the flotation of hematite using oleate, is studied here as a function of collector concentration, solution pH and ionic strength at various levels of conditioning temperature. The study revealed strong interactions between variables; particularly, the effect of conditioning temperature was found to strongly depend on the ionic strength of the solution. Thus, while an increase of conditioning temperature at lower ionic strengths or that of ionic strength at lower temperatures resulted in an increase of both flotation and grade, an increase of the former at higher ionic strength or that of the latter at higher temperatures caused a significant decrease in both responses. These observations have been explained in terms of the increased chemisorption of oleate at elevated temperatures and the temperature effect of ionic-strength on the salting out of the oleate from the bulk solution. The above effects which were first observed during Hallimond cell flotation tests were subsequently tested with Denver cell using low-grade iron ore. The results obtained using the two test procedures were in agreement with each other. The implications of these effects and interactions for process control of optimum flotation performance must be noted since variation in the levels of the above parameters are likely under plant conditions.